Epileptiform activity contralateral to unilateral hippocampal sclerosis does not cause the expression of brain damage markers. (21st May 2019) - Noè, Francesco; Cattalini, Alessandro; Vila Verde, Diogo; Alessi, Camilla; Colciaghi, Francesca; Figini, Matteo; Zucca, Ileana; de Curtis, Marco
Abstract: Objective: Patients with epilepsy often ask if recurrent seizures harm their brain and aggravate their epileptic condition. This crucial question has not been specifically addressed by dedicated experiments. We analyze here if intense bilateral seizure activity induced by local injection of kainic acid (KA) in the right hippocampus produces brain damage in the left hippocampus. Methods: Adult guinea pigs were bilaterally implanted with hippocampal electrodes for continuous video—electroencephalography (EEG) monitoring. Unilateral injection of 1 μg KA in the dorsal CA1 area induced nonconvulsive status epilepticus (ncSE) characterized by bilateral hippocampal seizure discharges. This treatment resulted in selective unilateral sclerosis of the KA‐injected hippocampus. Three days after KA injection, the animals were killed, and the brains were submitted to ex vivo magnetic resonance imaging (MRI) and were processed for immunohistochemical analysis. Results: During ncSE, epileptiform activity was recorded for 27.6 ± 19.1 hours in both the KA‐injected and contralateral hippocampi. Enhanced T1‐weighted MR signal due to gadolinium deposition, mean diffusivity reduction, neuronal loss, gliosis, and blood–brain barrier permeability changes was observed exclusively in the KA‐injected hippocampus. Despite the presence of a clear unilateral hippocampal sclerosis at the site of KA injection, no structural alterations were detected by MR and immunostaining analysis performed in the hippocampus contralateral to KA injection 3 days and 2 months after ncSE induction. Fluoro‐Jade and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining at the same time points confirmed the absence of degenerating cells in the hippocampi contralateral to KA injection. Significance: We demonstrate that intense epileptiform activity during ncSE does not cause obvious brain damage in the hippocampus contralateral to unilateral hippocampal KA injection. These findings argue against the hypothesis that epileptiform activity per se contributes to focal brain injury in previously undamaged cortical regions.